A Prospective Randomized Controlled Study to Compare, Intraoperative Ventilatory Parameters, Insertion Success Rate & Oropharyngeal Leak Pressure of Three Airway Devices the Esophageal-Tracheal Combitube, the EasyTube and the Laryngeal Tube-S - Aditya Kumar Chauhan; Hem Chandra Bhatt; Shailesh Kumar Lohani (Asian Journal of Medical Research, 2019)
Background: Securing and managing the airway is quintessential and perhaps the most critical aspect in practice of anaesthesiology. The present study was designed to evaluate and compare the efficacy of Combitube, EasyTube and the Laryngeal tube suction, when placed in their conventional positions, for general anaesthesia during elective non-laparoscopic surgeries using controlled ventilation.Subjects and Methods:A prospective randomized controlled study done on 90 patients undergoing elective surgery under general anaesthesia were enrolled into the study and were randomly allocated to the following three groups using computer generated random table. Group ETC (n=30): Patients whose airway was managed using Esophageal tracheal combitube, Group EzT (n=30): Patients whose airway was managed using Easy Tube and Group LTS (n=30): Patients whose airway was managed using Laryngeal tube suction. The time taken to insert the device was recorded in each instance in all the groups. For comparison of qualitative data, Chi square test was used. Bonferroni correction was applied for multiple comparisons. P value of < 0.05 was considered statistically significant.Results:When compared, use of Combitube, EasyTube and Laryngeal Tube Suction was associated with statistically similar intraoperative airway pressures, dynamic compliance, airway resistance, SpO2, and EtCO2 (p>0.05). Combitube and EasyTube resulted in significantly higher incidence of mucosal trauma detected by presence of blood on the device after its removal and an insignificant increase in incidence of postoperative sore throat (p>0.05). Combitube placement resulted in significantly higher incidence of postoperative dysphagia as compared to easy tube and laryngeal tube suction(p<0.05). But the nature of all these complaints was mild and no active intervention was required in any case.Conclusion: We concluded that based on our observations, if and when Combitube, EasyTube or Laryngeal Tube Suction is used for emergency airway management, it can be continued for conduct of general anaesthesia in surgeries of moderate duration.